2020
DOI: 10.1016/j.jseaes.2020.104466
|View full text |Cite
|
Sign up to set email alerts
|

Thermochronology of the highest central Asian massifs (Khan Tengri - Pobedi, SE Kyrgyztan): Evidence for Late Miocene (ca. 8 Ma) reactivation of Permian faults and insights into building the Tian Shan

Abstract: HAL is a multidisciplinary open access archive for the deposit and dissemination of scientific research documents, whether they are published or not. The documents may come from teaching and research institutions in France or abroad, or from public or private research centers. L'archive ouverte pluridisciplinaire HAL, est destinée au dépôt et à la diffusion de documents scientifiques de niveau recherche, publiés ou non, émanant des établissements d'enseignement et de recherche français ou étrangers, des labora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 132 publications
2
17
0
Order By: Relevance
“…The lack of younger apatite grains probably indicates a period of tectonic quiescence following the collision of the Qiangtang block. This is in agreement with the hypothesis that an extensive peneplanation surface was developed in the Tianshan belt and the surrounding areas during the Middle to Late Jurassic (e.g., Dumitru et al, 2001;Jolivet et al, 2010;De Grave et al, 2011;Morin et al, 2019;Rolland et al, 2020;He et al, 2021b).…”
Section: Thermo-tectonic History Of the East Junggarsupporting
confidence: 90%
See 2 more Smart Citations
“…The lack of younger apatite grains probably indicates a period of tectonic quiescence following the collision of the Qiangtang block. This is in agreement with the hypothesis that an extensive peneplanation surface was developed in the Tianshan belt and the surrounding areas during the Middle to Late Jurassic (e.g., Dumitru et al, 2001;Jolivet et al, 2010;De Grave et al, 2011;Morin et al, 2019;Rolland et al, 2020;He et al, 2021b).…”
Section: Thermo-tectonic History Of the East Junggarsupporting
confidence: 90%
“…Mid-to Late Cretaceous cooling events have been widely recognized in the Tianshan belt (e.g., Dumitru et al, 2001;Wang et al, 2009b;De Pelsmaeker et al, 2015;Tang et al, 2015;Nachtergaele et al, 2018;Glorie et al, 2019;Rolland et al, 2020), and were generally interpreted as a response to the farfield effects of the Lhasa-Qiangtang collision (120-90 Ma) and/ or Kohistan-Dras Arc collision (90-70 Ma) (Yin and Harrison, 2000;Rolland, 2002;Rehman et al, 2011;Kapp and DeCelles, 2019). A compressional regime in the mid-Cretaceous (120-100 Ma) is documented by coeval tectonic inversion of the Turpan-Hami Basin (e.g., Zhu et al, 2004Zhu et al, , 2006b.…”
Section: Thermo-tectonic History Of the Eastern Tianshanmentioning
confidence: 99%
See 1 more Smart Citation
“… (a) Apatite fission‐track (AFT) and (U‐Th)/He (AHe) single‐grain age histograms for sample P‐01. (b) AHe single‐grain histograms for the granite basement near the Peak Pobedi (Rolland et al., 2020). …”
Section: Low‐temperature Thermochronology Datamentioning
confidence: 99%
“…Abundant low‐temperature thermochronological studies have indicated that the Tianshan experienced punctuated denudation during the Meso‐Cenozoic and accelerated exhumation since ∼10 Ma (e.g., Glorie et al., 2011; Jepson et al., 2018a; Lü et al., 2020; Macaulay et al., 2014; Rolland et al., 2020). While low to moderate relief study areas predominantly record the Mesozoic denudation history of the Tianshan (e.g., De Grave et al., 2013; Gillespie et al., 2017; Glorie & De Grave, 2016; Glorie et al., 2010; Jolivet et al., 2010), recent studies have revealed that the granitic basement near fault zones in the highest mountains of the Tianshan (e.g., Peak Pobedi in Kyrgyzstan) as well as granitic clasts from modern moraines of the Tomor Glacier in China record younger apatite (U‐Th)/He (AHe) ages within the range of 5.0∼7.1 Ma (Jia et al., 2020; Rolland et al., 2020). Latter cooling ages correspond with the modelled timing of rapid deformation and exhumation (7∼5.5 Ma) of the South Tianshan as revealed by magnetostratigraphy (J. M. Sun et al., 2009) and tectonic deformation studies of the Kuqa Fold‐and‐Thrust Belt (KFTB) (Hubert‐Ferrari et al., 2007).…”
Section: Introductionmentioning
confidence: 99%